Fatty and mycolic acids of Mycobacterium malmoense. - Valero-Guillén, P (1988)
The fatty acids and mycolic acids of 16 clinical isolates of Mycobacterium malmoense were studied by gas chromatography and thin-layer chromatography. All strains contained 2-methyleicosanoic and 2,4,6-trimethyltetracosanoic acids and alpha-, alpha'-, and keto-mycolic acids. The reported findings suggest that lipid analysis is a very useful approach in the species identification of M. malmoense.